The measurement of compaction through field density test (FDT) in the embankment strata - Shafie, Mohd. Hafiz (2015)
The soil should have sufficient strength, be relatively incompressible so that future settlement will not be excessive, maintain a constant volume change against variable water content or other factors, be resistant to deterioration, and possess proper permeability. Standard test had been introduced to determine the compaction percentage especially at the embankment area. In the current practice in the construction industry, the Field Density Test (FDT) Sand Replacement is the best method in term of result obtained at the economic cost. The method has limitation of the scope which the test normally to be carry on the surface layer after the soil layer leveled and compacted. When the test is carried out in the embankment, the moisture content of soil will be effected the compaction value of the soil layer. To overcome this issue, some testing had been undertaken at the vicinity of cut ground area with the same method carried in the embankment area. In addition, the percentage of consolidation of soft soil under the embankment and strength characteristic of the embankment layer had been considered. The result showed that the cut ground obtained high moisture content average 28% higher the Optimum Moisture Content (OMC) and consequently resulting to a lower range of 90% compaction. On the other hand, the consolidation percentage of soft soil under the timeframe showed 82% and 85% at selected point respectively. Moreover, the embankment layer showed at the condition of stiff layer based on the Mackintosh Probe (MP) test carried out at the area. From the result it has been concluded that the adopted test is incorrect due to effect of the high moisture content in the soil. The consolidation process occurring and affect the micro crack in the embankment even though the soil layer in the embankment is stiff layer.